(3GdTeS GdcGTaI dTHgI GdadGSaI GdcGTaIs - (3YHO Gddg Hf Ydj Hf eMeO Hf CHj GdbGSe GdgGOj Edj GdMbs
(3ChdgG (B:s
(3GdMeO ddg GdPi dG BNQ defJgGg , ceG dG Chd deHOCg hHYO aSCdJfi Yf cTa eG YQV dc ef GdadGSaI s
(3BNQgG (B:s
(3Ydi CfG fbhd QHeG cGf dCUdM dge Ndbge ai GdhbJ GdPi NdbhG ajg Je Pdc Hef Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HMhGTjgG JUMjMGJs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDda GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdeYGQa GdYGeIs